(untitled) (Perner’s Contacts, 2020)
The paper deals with the comparison of costs related to access to the transport network in road and rail freight transport on selected sections in the conditions of the Slovak Republic. It analyzes costs on selected routes in terms of absolute and unit prices and compares factors affecting these costs.